Cadonilimab plus chemotherapy as first-line treatment for persistent, recurrent, or metastatic cervical cancer: a cost-effectiveness analysis - Xiang, Zuojuan; Li, Zhengxiong; Chen, Xiaojuan; Fu, Yingzhou (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has made significant advancements in cervical cancer (CC) treatment; however, its efficacy remains limited in programmed death ligand 1 (PD-L1)-negative patients. Cadonilimab, the first bispecific antibody targeting both programmed death 1 (PD-1) and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), demonstrated superior efficacy and manageable safety as a first-line treatment for persistent, recurrent, or metastatic CC (p/r/m CC) in the phase III COMPASSION-16 trial. Notably, it showed significant survival benefits in PD-L1-negative patients. This study aimed to evaluate its cost-effectiveness from the perspective of the Chinese healthcare system.MethodsA partitioned survival model was developed based on data derived from the COMPASSION-16 trial. The model utilized a 3-week cycle length and a 10-year time horizon. The primary outcomes included costs, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net monetary benefit (INMB), and incremental net health benefit (INHB). Additionally, sensitivity analyses, scenario analyses, and subgroup analyses were performed.ResultsThe cadonilimab plus chemotherapy regimen provided an additional 0.61 QALYs compared to chemotherapy alone, at an incremental cost of $42,486.54. This yielded an ICER of $70,220.88/QALY, exceeding the willingness-to-pay threshold of $38,042/QALY. The corresponding INMB and INHB were -$19,469.55 and -0.51 QALYs, respectively. Consequently, cadonilimab plus chemotherapy was not deemed to be cost-effective. Sensitivity analyses showed that the results remained consistent when each parameter varied within the predetermined range, indicating the model’s robustness. Subgroup analyses demonstrated no significant positive correlation between economic outcomes and PD-L1 expression levels. Notably, in the subgroup of patients who did not receive bevacizumab, cadonilimab plus chemotherapy emerged as a cost-effective alternative.ConclusionIn China, cadonilimab plus chemotherapy is not considered cost-effective compared to standard chemotherapy as a first-line treatment for the general p/r/m CC population. However, it represents a cost-effective option for patients ineligible for bevacizumab therapy.